2006
DOI: 10.1002/bip.20511
|View full text |Cite
|
Sign up to set email alerts
|

One‐pot synthesis in aqueous system for water‐soluble chitosan‐graft‐poly(ethylene glycol) methyl ether

Abstract: Chitosan is functionalized with poly(ethylene glycol) methyl ether (mPEG) at the amino and hydroxyl groups via a single step reaction in a homogeneous aqueous system. A chitosan aqueous solution obtained from the mixture of chitosan and hydroxybenzotriazole (HOBt) in water is a key factor in providing mild conditions to conjugate mPEG by using a carbodiimide conjugating agent. The reaction at ambient temperature for 24 h gives chitosan-g-mPEG with water solubility with mPEG content as high as 42%. This work de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 23 publications
(23 reference statements)
0
41
0
Order By: Relevance
“…The comparison of curve (a) (pure whiskers) with curve (c) (pegylated whiskers) shows the addition of a new peak at 1735 cm −1 (carbonyl groups) and an increase in the intensity of the peaks at 1650 cm −1 (amide groups), 1100 cm −1 (C–O–C) and 2871 cm −1 (C‐H bond), which suggests the grafting of mPEG . Yoksan et al .…”
Section: Resultsmentioning
confidence: 96%
“…The comparison of curve (a) (pure whiskers) with curve (c) (pegylated whiskers) shows the addition of a new peak at 1735 cm −1 (carbonyl groups) and an increase in the intensity of the peaks at 1650 cm −1 (amide groups), 1100 cm −1 (C–O–C) and 2871 cm −1 (C‐H bond), which suggests the grafting of mPEG . Yoksan et al .…”
Section: Resultsmentioning
confidence: 96%
“…The possible mechanism of the interaction and complexation is shown in Fig. 1, which was also reported by Fangkangwanwong and Dai based on NMR study [27][28][29]. The complexes existing as salt form not only increased the water solubility of both chitosan and HOBt but also activated the amino groups of chitosan to react with the active ester of CTPC.…”
Section: Chitosan-hobt Systemmentioning
confidence: 59%
“…Finally, O-acylisourea reacted with A or B and the coupling reaction probably occur at C-2 to form an amide linkage. It was noted that the HOBt used in chitosan-HOBt system could also reduce the amount of generated N-acylisourea and moderate the reaction rate of the coupling reaction [29].…”
Section: Chitosan-hobt Systemmentioning
confidence: 99%
“…In general, HOBt is a conjugation additive for water soluble conjugation system. In the past, we found that HOBt forms an organic salt with chitosan as observed by 1 H NMR and enables chitosan to be a water soluble one [31,32]. There, the function of HOBt may not only activate the amino group of chitosan but also retarding the hydrogen bond of chitosan with the bulkiness of HOBt.…”
Section: Functionalization Of Chitosan Onto Pe Filmmentioning
confidence: 93%